2022
DOI: 10.1039/d1nj06000g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of chiral aryl alcohols: a controllable enzymatic strategy via light-driven NAD(P)H regeneration

Abstract: Controllable and mild photoenzymatic production of chiral alcohols was realized by coupling a versatile photochemical NAD(P)H regeneration system with (R)- or (S)-selective ketoreductases. The efficiency of NAD(P)H regeneration was improved...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In this study, a photocatalytic cofactor regeneration system coupled with various KRs like Ch KR20, Ch KR14, Ch KR03 LK ADH, and Ch KR20-M135 was utilized for the asymmetric reduction of various acetophenones to produce both ( R )- and ( S )-phenyl ethanols in good yield (up to 97%) with excellent ee (up to >99%). 101 Thus, the use of these recombinant strains provides an efficient alternative to the conventional chemical synthesis of various industrially important chiral precursors.…”
Section: Recombinant Enzymes In Redox Biocatalysismentioning
confidence: 99%
“…In this study, a photocatalytic cofactor regeneration system coupled with various KRs like Ch KR20, Ch KR14, Ch KR03 LK ADH, and Ch KR20-M135 was utilized for the asymmetric reduction of various acetophenones to produce both ( R )- and ( S )-phenyl ethanols in good yield (up to 97%) with excellent ee (up to >99%). 101 Thus, the use of these recombinant strains provides an efficient alternative to the conventional chemical synthesis of various industrially important chiral precursors.…”
Section: Recombinant Enzymes In Redox Biocatalysismentioning
confidence: 99%
“…33 However, Rh-based cocatalysts are usually free in photocatalytic nicotinamide cofactor regeneration systems, leading to longer electron transfer and lower contact probability between the photocatalyst surfaces. 34,35 The integration of M into the photocatalyst is an effective method to solve this problem. 33,35−37 The chemical structures of COFs with programmable modules can easily introduce the bipyridine group to immobilize M, and a properly designed COF-Rh structure can obtain good photocatalytic activity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Photocatalysts with hollow structures can trap more incident photons through multiple scattering, thus enhancing light harvesting. Typically, cocatalysts (especially [Cp*Rh­(bpy)­H 2 O] 2+ , abbreviated as M ) were added to intensify the electron utilization . However, Rh-based cocatalysts are usually free in photocatalytic nicotinamide cofactor regeneration systems, leading to longer electron transfer and lower contact probability between the photocatalyst surfaces. , The integration of M into the photocatalyst is an effective method to solve this problem. , The chemical structures of COFs with programmable modules can easily introduce the bipyridine group to immobilize M , and a properly designed COF-Rh structure can obtain good photocatalytic activity. , Therefore, the preparation of COF-Rh into hollow structures and S-scheme heterojunctions by coupling COF to COF is expected to yield higher efficiency of photocatalytic cofactor regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] It has been shown that a rhodium complex [Cp*Rh(bpy)Cl] Cl (M, Cp* = pentamethylcyclodienyl; bpy = bipyridine,) and its derivatives are currently one of the important electron mediators that enable efficient regeneration of photocatalytic NAD(P)H. [27][28][29][30] Currently, in most of the reported photocatalytic systems, M is dissolved in the reaction medium alone, which not only reduces the electron transfer efficiency but also the homogeneous M tends to poison the enzyme and reduce the reaction efficiency. [6,8] In our previous work, [31] M was immobilized on MOF by covalent linkage for regulating and controlling electron transfer and electron utilization, which effectively improved the regeneration efficiency of NAD(P)H. Integrating the electron mediator and photosensitizer in the MOF can shorten the distance between them and ensure the direct transfer of photogenerated electrons from the photosensitizer to M, similar to chloroplasts. [14,20,32] Herein, we selected the UiO-66-NH 2 for integration of tetra topic porphyrin ligands (TCPP), electron mediators (M), and FDH to assemble a prototypical semi-artificial photosynthetic system for the first time.…”
Section: Introductionmentioning
confidence: 99%